Nitrificación potencial en agroecosistemas del Ebro Medio - Badia D.; Alcañiz J.-M. (Jornadas sobre las bases ecológicas para la gestión en ecosistemas terrestres, 1989)
Seasonal samples from six experimental plots of saline, gypseous and carbonated soils from arid lands of Ebro Valley, under irrigated and non-irrigated conditions, were incubated 14 days to determinate the potential nitrate production. Analytical data point out a decrease of nitrifying activity on saline soil plots. Nevertheless, the nitrate content is higher on these saline soils mostly due to few outputs. Seasonal changes and high spring nitrification activity were detected.
Jornadas sobre las Bases Ecológicas para la Gestión en Ecosistemas Terrestres, 1988/06/13-15, Zaragoza (Spain)